Single-snip paralimbal incision: A quick approach to rectus muscles - Saxena, Juhi (Oman J Ophthalmol, 2021)
INTRODUCTION: Less invasive and quicker surgeries have become common. We compared two conjunctival incisional approaches in strabismus, namely Follow standard paralimbal approach for (SPLA) and single-snip paralimbal (SSPLA). MATERIALS AND METHODS: Forty-four patients with horizontal strabismus qualifying for uniocular recession–resection surgeries were randomized to SPLA and SSPLA. SSPLA involved a single v-shaped incision, with the apex of the V near the limbus, and the limbs facing away: by pinching up the conjunctiva with a forceps and delivering the single snip with a spring scissors. We compared the postoperative grades of redness, congestion, chemosis, foreign body sensation, and drop intolerance at day 1, 2 weeks, and 6–8 weeks; scar visibility, as yes or no, at 6–8 weeks; success rates, considered to be within 10 prism diopters of orthophoria, at 6–8 weeks; and operation duration in minutes. STATISTICAL ANALYSIS: Statistical analysis was done using Mann–Whitney U-test, for inflammatory grades, Chi-square for proportions, and t-test for parametric measures. Statistical significance was set at P < 0.05. RESULTS: On postoperative day 1, congestion (P = 0.02), foreign-body sensation (P = 0.04), and total inflammatory score (P = 0.003) were statistically significantly favoring the SSPLA group. While at 2 weeks, only congestion (P = 0.02) was found to be significantly less in the SSPLA group. There were no significant differences in the proportions of scar visibility (5/22 in the SPLA vs. 3/22 in the SSPLA) and success rate: 20/22 vs. 18/22. The SSPLA was quicker on an average by 6 min (P < 0.001, 95% confidence interval: 3.2–8.7). CONCLUSION: Compared to the SPLA, the SSPLA is quicker and results in lesser inflammation in the immediate postoperative period.